Peningkatan Perilaku Inovatif Perajin Tenun Melalui Perilaku Berbagi Pengetahuan dan Efikasi Diri - Sulistiowati, Sulistiowati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
Innovation is needed for creative businesses, especially crafts. Innovative behavior is closely related to innovation. This study aims to analyze the influence of knowledge sharing on the innovative behavior of weaving crafters and how the effect of self-efficacy on the innovative behavior of weaving crafters. The study was conducted on 50 weaving craftsmen in Sambas Regency, Kalimantan Barat Province. The conclusion of descriptive statistical analysis is the innovative behavior of weaving crafters in the very high category, knowledge sharing behavior in high category, and self efficacy in the very high category. Hypothesis testing is done by multiple regression analysis, with SPSS 20.0 software. The results of this study concluded that there was no significant influence of knowledge sharing behavior on the innovative behavior of weaving crafters, and there was a significant effect of self-efficacy on the innovative behavior of weaving crafters.